A genetic association study in the Gambia using tagging polymorphisms in the major histocompatibility complex class III region implicates a HLA-B associated transcript 2 polymorphism in severe malaria susceptibility. - Diakite, M; Clark, T; Auburn, S; Campino, S; Fry, A; Green, A; Morris, A; Richardson, A; Jallow, M; Sisay-Joof, F; Pinder, M; Kwiatkowski, D; et al. (2009)
The tumour necrosis factor (TNF) gene and other genes flanking it in the major histocompatibility complex (MHC) class III region are potentially important mediators of both immunity and pathogenesis of malaria. We investigated the association of severe malaria with 11 haplotype tagging-polymorphisms for 11 MHC class III candidate genes, including TNF, lymphotoxin alpha (LTA), allograft inflammatory factor 1 (AIF1), and HLA-B associated transcript 2 (BAT2). An analysis of 2,162 case-controls demonstrated the first evidence of association between a BAT2 polymorphism (rs1046089) and severe malaria.